Photocatalytic hydrogen production by direct sun light from sulfide/sulfite solution - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2002)
The photocatalytic hydrogen production from a sulfide/sulfite solution is one of the photocatalytic processes that have been of interest recently for hydrogen production. Different types of semiconductor photocatalysts have been prepared and tested for this purpose, In this paper, photocatalysts CdS/ZnS that were prepared by a different coprecipitation technique was studied with and without n-Si in sulphide/sulphite solution irradiated with direct sunlight at laboratory level. From the study of variation in composition of CdS/ZnS, 2:1 (by weight) composition was found to be very efficient for hydrogen production. The rate of hydrogen liberation was achieved by addition of n-Si. The maximum hydrogen has been produced with the photocatalyst CdS/ZnS/n-Si (2/1/1.4-1.6%). The recorded maximum hydrogen evolution rate was 35.5 ml h(-1) g(-1) in 250 ml 0.24 M Na2S and 0.35 M Na2SO3 solution. (C) 2002 International Association for Hydrogen Energy, Published by Elsevier Science Ltd. All rights reserved.
Keywords: hydrogen; photoproduction; CdS/ZnS; photocatalyst; PHOTOELECTROCHEMISTRY; CATALYST; SULFIDE; CDS